Characterization of PM2.5 at a traffic site using several integrated analytical techniques. (14th October 2020) - Hamdan, Nasser M.; Alawadhi, Hussain; Shameer, Mohamed
Abstract : We have conducted a comprehensive, year‐long, sampling campaign for particulate matter (PM) at a site near a major highway, following standard protocols. Total mass, elemental and chemical composition of the fine fractions (PM2.5 ) of particulates originating from traffic are determined using several complementary techniques. These complementary techniques include gravimetric analysis, X‐ray fluorescence, scanning electron microscopy and energy dispersive spectroscopy, X‐ray diffraction (XRD) and black carbon multiwavelength absorption. Conducting an enrichment factor analysis and correlation coefficient calculations on elements show that Si, Ca, Al, Fe, Ti, Mn, Mg, K, Na and Cr are of crustal origin, while P, Cl and V are enriched slightly from human activities. All other measured elements (Rb, Zr, Ba, Sr, S, Ni, Cu, Zn and Pb) have high enrichment factors and relate to anthropogenic sources. Sulfates in the form of mascagnite and koktaite had the largest contribution to PM2.5 (43% of total PM concentration). Natural pollutants such as quartz, calcite, iron oxide and aluminum oxide originating from the crust also contribute to PM2.5 . eBC and elements such as Zn, Ba, Cu, Fe and S are related to traffic emissions such as exhaust emissions and tire, brakes and road erosion. Correlation coefficients and enrichment factor calculations helped identify elements that are related to natural emissions and those related to anthropogenic sources. Being an arid region, the PM2.5 mass concentrations were found to be within or slightly above international air quality standards.